Subtropical Brazilian mangroves as a refuge of crab (Decapoda: Brachyura) diversity - Colpo, Karine Delevati [UNESP]; Chacur, Monica Mungai; Guimaraes, Fernanda Jordao; Negreiros-Fransozo, Maria Lucia [UNESP] (Springer, 2011)
This study characterized seven mangrove areas of different sizes, located on the southeastern Brazilian coast, with respect to their sediment and vegetation features. We also estimated the richness and composition of the brachyuran assemblages in these mangroves. Crab, vegetation and sediment data were collected during low tide. The larger mangroves showed richer and complex forests, and may be more ecologically stable than smaller mangroves. Twenty-eight species of crabs were recorded, members of nine families: Panopeidae, Pinnotheridae, Gecarcinidae, Grapsidae, Sesarmidae, Varunidae, Ocypodidae, Ucididae, and Portunidae. Ocypodoidea predominated over Grapsoidea in the smaller mangrove areas in pioneer stages of forest establishment, whereas the opposite was recorded for larger and more stable mangroves, where the forest can reach advanced stage of development. Comprido is a small mangrove, but its crab assemblage was similar to the larger ones, probably because of other factors not investigated here (e.g., megalopa settling rate). This study provided basic knowledge for developing conservation strategies for vulnerable mangrove ecosystems.
Keywords: Brazil; Crab assemblages; Forest features; Sediment; Subtropical mangroves